2018
DOI: 10.3171/2017.11.focus17581
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the techniques of direct pars interarticularis repairs for spondylolysis and low-grade spondylolisthesis: a meta-analysis

Abstract: OBJECTIVESpondylosis with or without spondylolisthesis that does not respond to conservative management has an excellent outcome with direct pars interarticularis repair. Direct repair preserves the segmental spinal motion. A number of operative techniques for direct repair are practiced; however, the procedure of choice is not clearly defined. The present study aims to clarify the advantages and disadvantages of the different operative techniques and their outcomes.<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 46 publications
1
49
1
9
Order By: Relevance
“…It is very important for healing of spondylolysis and symptoms recovery. The union rate of this method was higher than those described in previous reports [ 4 ]. With reference of CT classification, all the type I cases healed at 9 months, but the slowest healing occurred in type III cases.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…It is very important for healing of spondylolysis and symptoms recovery. The union rate of this method was higher than those described in previous reports [ 4 ]. With reference of CT classification, all the type I cases healed at 9 months, but the slowest healing occurred in type III cases.…”
Section: Discussioncontrasting
confidence: 65%
“…Surgical methods for lumbar spondylolysis could be roughly divided into two categories, fusion and repair. Meaningless sacrifice of fairly normal disc and segmental motion make stricter indication for fusion [ 4 7 ]. The concept of repair surgery is similar to osteosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in the years following Buck's conception of bilateral screw trajectory, other techniques for internal vertebral fixation have also emerged, such as the use of cerclage wires as proposed by Scott and published by Bradford (1976) and the securing of hooks underneath the lamina as conceptualized by Morscher (1984) [13][14][15] . However, a comparative meta-analysis of Buck's, Scott's, and Morscher's technique has revealed that Buck's technique had the highest rate of fusion (83.53%), followed by Scott's (81.57%) and finally Morcher's (77.72%) 16 .…”
Section: First Conceptualizationmentioning
confidence: 99%
“…Практически все исследователи единодушны во мнении, что наличие спондилолиза является фактором высокой степени риска формирования спондилолистеза, который в этих случаях, по используемым в настоящее время классификациям, следует относить к спондилолизному (истмическому) [11,12,32,38,[47][48][49][55][56][57][58]. Вероятность формирования такой формы спондилолистеза при наличии спондилолиза составляет не менее 50-70% [47,48,59,60].…”
Section: материал и методыunclassified
“…Основной целью операции является удаление фиброзной ткани из зоны спондилолиза и достижение в этой области костного сращения посредством применения костной аутопластики и (или) остеосинтеза различными металлоконструкциями [38,71]. В случае оперативного лечения спондилолизного спондилолистеза в настоящее время «золотым стандартом» принято считать транспедикулярный спондилодез в сочетании с передним спондилодезом имплантатами различных конструкций после удаления дегенеративно измененного межпозвонкового диска и замыкательных пластин тел смежных позвонков [11,47,56,75,76]. Превентивное оперативное лечение зоны спондилолиза, в том числе многоуровневого, по мнению j. Mo с соавторами, нецелесообразно, так как может привести к «биомеханическим сдвигам и потере устойчивости позвоночника» [77].…”
Section: материал и методыunclassified